Novel daidzein molecules exhibited anti-prostate cancer activity through nuclear receptor ERβ modulation, in vitro and in vivo studies. (24th November 2021) - Ranjithkumar, R.; Saravanan, K.; Balaji, B.; Hima, S.; Sreeja, S.; Timane, S. R.; Ram Pravin Kumar, M.; Kabilan, S.; Ramanathan, M.
Abstract : Eight novel ERβ selective daidzein analogues (NCE1-8) were synthesized and their anti-cancer activity was evaluated by in vitro and in vivo methods. Cytotoxicity study, Receptor binding studies, Luciferase assay, cMYC & Cyclin D1 expression and Caspase 3, 8 & 9 activities were measured to ascertain the anticancer activity and mechanism. Uterotropic, anti-androgenic and anti-tumour activities were performed in rodents. The results revealed that NCEs produced anti-prostate cancer activity in DU145, LNCaP and PC3 cell lines and 50% more active than genistein. NCEs was significantly down-regulated cMYC & Cyclin D1 genes and elevated caspase 3 & 9 levels and did not show any difference in uterotropic, anti-androgenic activities. The tumour weight was also reduced. The NCE 1 and 2 have shown ERβ selectivity in receptor binding studies. Daidzein with methyl substitution at R or R1 position exhibited more ERβ selectivity and could be considered as lead molecules for anti-prostate cancer activity.